Addressing Academic Anxiety Among Students from Broken Families: Exploring an Islamic Counselling Approach Grounded in Javanese Indigenous Values - Marhamah, Uswatun; Syukur, Fatah; Panuntun, Slamet; Choirudin, Moch; Hakim, Abdul (Islamic Guidance and Counseling Journal, 2026)
Adolescents from divorced or conflict-affected families in Indonesia often experience academic anxiety rooted in emotional instability and limited family support. This challenge is especially pronounced in Javanese cultural settings, where harmony, acceptance, and spiritual balance are central to well-being. However, research on school counselling in Indonesia remain largely generic, often neglecting these cultural and spiritual dimensions that shape students’ emotional resilience. To address this gap, the present study explores the Junggringan Kawruh Jiwo (JKJ) counselling method, a culturally grounded approach that integrates Islamic spirituality and Javanese indigenous values to support students from broken families in managing academic anxiety. JKJ combines Ki Ageng Suryomentaram’s concept of kawruh jiwa (self-awareness and emotional responsibility), Islamic spiritual practices (dhikr, prayer, and reflection on Qur’anic verses), and Javanese principles (nrimo, ngalah, sabar) into a holistic therapeutic framework. Six students (aged 16-18) from divorced or conflict-affected families and three experienced school counsellors, purposively recruited through school administrations based on their prior work with such students, participated from three vocational schools in Semarang, Indonesia. Data were collected through in-depth interviews, participant observation, and analysis of reflective journals (February-April 2025). Credibility was enhanced through triangulation across data sources and validation via member checking and expert consultation in Javanese cultural and counselling traditions. Data were collected through in-depth interviews, participant observation, and reflective journal analysis between February and April 2025. Credibility was enhanced through triangulation of data sources and verification of interpretations via member checking and expert consultation in Javanese culture and counselling practice. The findings reveal that JKJ counselling enabled students to recognise and regulate anxiety through reflective dialogue, spiritual practices, and culturally resonant exercises promoting acceptance and self-awareness. Counsellors’ empathetic engagement fostered emotional safety and trust. Collectively, these results indicate that JKJ represents a culturally responsive counselling framework with potential to enhance the psychological support available to adolescents from broken families in Indonesia.